On the detachment of hydrophobic particles from the froth phase. (September 2016) - Moreno, Yesenia Saavedra; Ata, Seher
Highlights: A new experimental set-up has been developed to study detachment of particles from the froth phase. The fraction of particles detaching from the froth decreases exponentially with increase in the collector concentration. The dropback values obtained in the present system are considerably lower than the previously reported values. Abstract: We conducted an experimental study to investigate the behaviour of hydrophobic particles in the froth phase of a laboratory column. A stable froth was formed by passing the air through a porous disk into the liquid containing frother. Individual bubbles were loaded with hydrophobic particles separately in a fluidised bed and allowed to rise into the froth layer. Particles dislodged from the froth were collected and measured. The effect of collector concentration and superficial gas velocity on the detachment of particles from the froth was studied. The results showed that fraction of particles detaching from the froth decreases exponentially with increase in the collector concentration and increases slightly with superficial gas velocity. In general, low froth dropback values were obtained for the conditions studied in the present system which are considerably lower than the previously reported values.